2017
DOI: 10.1021/acs.orglett.7b00562
|View full text |Cite
|
Sign up to set email alerts
|

An Organic Intermolecular Dehydrogenative Annulation Reaction

Abstract: The discovery of a direct method for the synthesis of three-ring heterocyclic carbazoles from unactivated arenes and anilides by a metal-free (organic) intermolecular dehydrogenative annulation reaction under ambient laboratory conditions is reported. Iodine(III) was used as the sole reagent either stoichiometrically from inexpensive phenyliodine diacetate or organocatalytically by in situ generation from PhI-mCPBA. In a single step, three C(sp)-H bonds and one N(sp)-H bond are functionalized from two differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 45 publications
(37 reference statements)
0
38
0
Order By: Relevance
“…In a continuation of our research interests towards controlling chemical reactions using weak interactions in nonprefunctionalized aromatic systems, in this paper we report an intramolecular C(sp 2 )–H amidation reaction (Figure c) for the synthesis of 1,2‐disubstituted benzimidazoles using NIS instead of a strong oxidant like phenyliodine diacetate (PIDA) . To date, numerous methods for the synthesis of N–H benzimidazoles have been established, but very few reports of the metal‐free direct synthesis of N ‐substituted benzimidazoles are known …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a continuation of our research interests towards controlling chemical reactions using weak interactions in nonprefunctionalized aromatic systems, in this paper we report an intramolecular C(sp 2 )–H amidation reaction (Figure c) for the synthesis of 1,2‐disubstituted benzimidazoles using NIS instead of a strong oxidant like phenyliodine diacetate (PIDA) . To date, numerous methods for the synthesis of N–H benzimidazoles have been established, but very few reports of the metal‐free direct synthesis of N ‐substituted benzimidazoles are known …”
Section: Resultsmentioning
confidence: 99%
“…Through the addition of the acid salt NaHSO 4 , the reactivity of the amine nitrogen towards iodine(III) was decreased by charge transfer. We have also recently shown that sulfonamide‐protected arylamines react in 2,2,2‐trifluoroethanol (TFE) to give carbazoles . Certain arylamines also reacted exothermically with PIDA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[14] Many chemical reactions are well known to be controlled by weak interactions. [26] In continuation of our research focus towards the use of hypervalent iodine reagents in organic synthesis, [27] herein we report an intermolecular dehydrogenative aryl CÀS coupling reaction [28] for the synthesis of diaryl sulfides and aryl sulfinyl arenes (or diaryl sulfoxides) from the respective arenes and thiophenols via generation of sulfenium ion. Selective examples of the weak interactions like anionp, [16] cation-p, [17] charge-transfer, [18] halogen bonding, [19] hydrophobic effect, [20] etc.…”
Section: Introductionmentioning
confidence: 99%